Blade tenderization in combination with injection enhancement containing an enzyme increases tenderness of strip steaks from fed cull cows - Stacy L. Hutchinson; M.J. Daniel; James J. Higgins; John A. Unruh; Melvin C. Hunt (Kansas Agricultural Experiment Station Research Reports, 2008)
Cow meat is tougher than meat from young steers and heifers and typically has a less desirable, darker color. It is generally assumed that cow meat will need to be ground or have some form of post-mortem tenderization applied to be merchandized as a whole muscle product. Most cow steaks are fabricated by food service providers for their customers with different specifications for aging and post-mortem tenderization application. Aging, blade tenderization, and injection enhancement are commonly used on cow meat to increase tenderness. It is unknown if an extended aging period is needed in addition to a combination of tenderization and injection enhancement to improve tenderness. If shorter aging periods can be used without compromising tenderness, then aging costs would be greatly reduced. Our objective was to determine the effects of days of aging and an enhancement protocol on tenderness of strip loin steaks from fed cull cows.
Keywords: Cattlemen& #x27; s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Increase tenderness; Blade tenderization; Injection enhancement